Islamic Cultural Studies 2000–2025: Knowledge Domains, Key Conversations, and Emerging Themes - Judijanto, Loso (Westscience Press, 2026)
The purpose of this research is to perform intellectual mapping of the academic discourse of the field of Islamic Cultural Studies from 2000 to 2025 using the bibliometric method. To achieve this aim, data was collected from the Scopus database. Moreover, this study employed VOSviewer software to analyze the author collaboration network, citation behavior and co-word analysis. It was found that the author collaboration network of Islamic Cultural Studies is geographically dispersed in nature, with a number of researchers from Southeast Asia countries like Indonesia and Malaysia making considerable contribution. The result of citation behavior analysis showed that Islamic Cultural Studies is an interdisciplinary field covering topics such as Political Islam, Gender, Identity, and Islamic Work Ethics. Through the use of keyword analysis, it was established that the core concepts like Islam, Religion, Culture and many others were dominating in Islamic Cultural Studies. However, there are some emerging topics like Islamic Education, Cultural Heritage, Identity and Islamism. Through overlay and density visualization, it was concluded that the field of Islamic Cultural Studies has shifted its focus from behavioral analysis at the micro level to sociocultural analysis.